2022
DOI: 10.6018/red.507701
|View full text |Cite
|
Sign up to set email alerts
|

La comparación del enfoque STEM y el modelo de aprendizaje SSCS para la escuela secundaria basado en el plan de estudios K-13: el impacto en la capacidad de pensamiento creativo y crítico

Abstract: In the 21st century, the significance of competencies is increasing in our everyday lives and in the labor market. Such complex competencies like critical and creative thinking is a topic that are becoming more and more relevant. In the past, researchers have shown a direct link between creative thinking and teaching methods. The project will apply a STEM research method throughout the study and comparing SSCS learning. The study focuses on the critical examination of specific assignments and students' critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(39 reference statements)
0
4
0
4
Order By: Relevance
“…SSCS merupakan salah satu model pembelajaran yang menggunakan pendekatan pemecahan masalah (Diani et al, 2019). Model ini terbagi menjadi empat tahap yaitu: (1) tahap pencarian (Search), mencakup konsep-konsep lain yang menyederhanakan dan mengidentifikasi serta mengembangkan pertanyaan atau masalah yang diteliti, (2) tahap penyelesaian (Solve), fokus diberikan pada masalah spesifik lalu siswa diminta untuk merancang dan menerapkan rencana untuk menyelesaikannya, (3) tahap menciptakan (create), siswa juga didorong untuk membuat produk yang terkait dengan masalah, membandingkan data dengan masalah, membuat generalisasi, dan memodifikasinya jika perlu, dan (4) tahap berbagi (Share), tahap ini melibatkan siswa dalam mengkomunikasikan solusi untuk masalah atau jawaban dari pertanyaan yang diajukan (Maskur et al, 2022).…”
Section: Model Pembelajaran Sscsunclassified
“…SSCS merupakan salah satu model pembelajaran yang menggunakan pendekatan pemecahan masalah (Diani et al, 2019). Model ini terbagi menjadi empat tahap yaitu: (1) tahap pencarian (Search), mencakup konsep-konsep lain yang menyederhanakan dan mengidentifikasi serta mengembangkan pertanyaan atau masalah yang diteliti, (2) tahap penyelesaian (Solve), fokus diberikan pada masalah spesifik lalu siswa diminta untuk merancang dan menerapkan rencana untuk menyelesaikannya, (3) tahap menciptakan (create), siswa juga didorong untuk membuat produk yang terkait dengan masalah, membandingkan data dengan masalah, membuat generalisasi, dan memodifikasinya jika perlu, dan (4) tahap berbagi (Share), tahap ini melibatkan siswa dalam mengkomunikasikan solusi untuk masalah atau jawaban dari pertanyaan yang diajukan (Maskur et al, 2022).…”
Section: Model Pembelajaran Sscsunclassified
“…Previous research supports the importance of mathematical thinking skills. A study by the Maskur et al (2022) found that mathematical thinking skills are crucial for success RED. Revista de Educación a Distancia.…”
Section: Mathematical Thinking Skills In 4csmentioning
confidence: 99%
“…This curriculum for independent learning was designed as a curriculum framework that is more adaptable and focuses on content and character development as well as learner competencies. The purpose of this independent learning program is to give schools, teachers, and students the freedom to innovate and determine actions in the process of teaching and learning activities, so that teachers and schools are encouraged to avoid monotony and can accommodate the overall characteristics of students from diverse backgrounds (Maskur et al, 2022;Ministry of Education and Culture, 2014;Suherman & Vidákovich, 2022).…”
Section: Digital Literacymentioning
confidence: 99%
“…Kerja proyek adalah suatu produk yang berupa laporan tertulis atau lisan, presentasi atau rekomendasi (Maskur et al, 2022). Contoh pada materi rantai makanan peserta didik menghasilkan proyek berupa bagan gambar rantai makanan ekosistem di lingkungan sekolah seperti ekosistem kebun, kolam dan sebagainya.…”
Section: Hasil Dan Pembahasanunclassified